Coefficient Inequality for Sakaguchi kind of Functions Related to Shell – like Curves Connected with Fibonacci numbers - et al., P.Lokesh (International Journal of Advanced Science and Technology, 2019)
In this paper, the Taylor-Maclaurin coefficients and of the two new subclasses of bi univalent of Sakaguchi kind of functions related to shell – likes curves connected with Fibonacci numbers in the open unit disk have been investigated. Further Fekete – Szego inequalities for these classes are determined. 2010 Mathematics Subject Classification: 30C45, 30C50.